2008
DOI: 10.1029/2008jd010140
|View full text |Cite
|
Sign up to set email alerts
|

Absorbing aerosols over Asia: A Geophysical Fluid Dynamics Laboratory general circulation model sensitivity study of model response to aerosol optical depth and aerosol absorption

Abstract: [1] Forcing by absorbing atmospheric black carbon (BC) tends to heat the atmosphere, cool the surface, and reduce the surface latent and sensible heat fluxes. BC aerosol can have a large impact on regional climates and the hydrologic cycle. However, significant uncertainties remain concerning the increases in (1) the total amount of all aerosol species and (2) the amount of aerosol absorption that may have occurred over the period. Focusing on south and east Asia, the sensitivity of a general circulation mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
96
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(102 citation statements)
references
References 64 publications
4
96
0
Order By: Relevance
“…Such aerosol-radiation interactions lead to large reductions of surface insolation and significant radiative heating of the atmosphere (Ramanathan and Carmichael, 2008;Johnson et al, 2008a;Malavelle et al, 2011;Milton et al, 2008). These effects may suppress the hydrological cycle by stabilizing the lower troposphere, although strong absorption can in some cases enhance precipitation regionally by increasing low-level convergence (Wu et al, 2013;Ramanathan et al, 2001;Lau et al, 2008;Randles et al, 2008). The enhancement of particulate numbers by BB can also increase the concentration of cloud condensation nuclei modifying cloud microphysical properties (Spracklen et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Such aerosol-radiation interactions lead to large reductions of surface insolation and significant radiative heating of the atmosphere (Ramanathan and Carmichael, 2008;Johnson et al, 2008a;Malavelle et al, 2011;Milton et al, 2008). These effects may suppress the hydrological cycle by stabilizing the lower troposphere, although strong absorption can in some cases enhance precipitation regionally by increasing low-level convergence (Wu et al, 2013;Ramanathan et al, 2001;Lau et al, 2008;Randles et al, 2008). The enhancement of particulate numbers by BB can also increase the concentration of cloud condensation nuclei modifying cloud microphysical properties (Spracklen et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…It is important to note, however, that climate forcing by anthropogenic aerosols may not always reduce precipitation. Both Lau and Kim (2006) and Randles and Ramaswamy (1997) find substantial increases in convection over east Asia resulting from higher tropospheric concentrations of absorbing aerosols. The authors attribute precipitation increases to changes in monsoon circulation and increases in mid-troposphere stability.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the atmosphere becomes unstable due to the BC semi-direct effect, leading to increased cloud water and precipitation. Menon et al (2002) and Randles and Ramaswamy (2008) indicated the precipitation may increase in Asia due to the semidirect effect of BC. On the other hand, cloud water and precipitation decrease in central and southern Africa, Central America, and the Amazon during the biomass burning seasons.…”
Section: Resultsmentioning
confidence: 99%